The Relationship Between Emotional Intelligence and Learning Outcomes of Economic Subjects in The Package C Program at SKB 1 Tanah Datar - Nadhira Ulfa; Wirdatul 'Aini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The background to this research is the low learning outcomes of students studying economics in the package C learning program at SKB 1 Tanah Datar. This is thought to be due to the low emotional intelligence of students studying. This research aims to: 1) describe the description of the emotional intelligence of students studying package C at SKB 1 Tanah Datar, 2) describe the description of the learning outcomes of students studying economics in the package C program at SKB 1 Tanah Datar, 3) to determine the relationship between emotional intelligence residents study with the results of studying economics subjects in the package C program at SKB 1 Tanah Datar. This research was carried out with a correlational quantitative approach which aims to test the relationship between emotional intelligence and learning outcomes in economics subjects in the package C program at SKB 1 Tanah Datar consisting of 39 students. The sampling technique was simple random sampling and 80% were taken. namely 30 people studied and as many as 20% were used as trials, namely 9 people. The data collection method uses a questionnaire with a statement list format as a data collection tool, the data analysis technique uses a percentage formula and to find correlations uses the Rank Order formula. The results of the research illustrate that: 1) the emotional intelligence of students studying in the package C program at SKB 1 Tanah Datar is categorized as low, 2) the learning outcomes for economic subjects in the package C program at SKB 1 Tanah Datar are categorized as low because many students' grades are below the KKM, and 3) there is a significant relationship between emotional intelligence and learning outcomes in economics subjects in the package C program at SKB 1 Tanah Datar. Keywords: Emotional Intelligence; Learning outcomes